Management of hyperhidrosis - Stashak AB; Brewer JD (Dove Medical Press, 2014)
Anna-Bianca Stashak,1 Jerry D Brewer2 1Internal Medicine Residency Program, Loma Linda University Medical Center, Loma Linda, CA, USA; 2Division of Dermatologic Surgery, Department of Dermatology, Mayo Clinic, Rochester, MN, USA Abstract: Primary hyperhidrosis (HH), a condition of sweating in excess of thermoregulatory requirements, affects nearly 3% of the US population and carries significant emotional and psychosocial implications. Unlike secondary HH, primary HH is not associated with an identifiable underlying pathology. Our limited understanding of the precise pathophysiologic mechanism for HH makes its treatment particularly frustrating. However, a wide array of interventions for the treatment of HH have been implemented throughout the world. Herein, we discuss the most extensively studied therapeutic options for primary HH, including systemic oxybutynin, botulinum toxin injections, skin excision, liposuction–curettage, and sympathotomy/sympathectomy. We conclude with a discussion of possible future therapies for HH, including the applications of laser, microwave, and ultrasound technologies. Keywords: primary hyperhidrosis, secondary hyperhidrosis, eccrine ducts, botulinum toxin, surgery, laser